Human gender identification using permittivity of urine / Sorour Zhola Zadeh Saki - Sorour Zhola, Zadeh Saki (2012)
Study on gender identification is one of the interesting issues, which helps researchers to learn more about disease pathogenesis and to discover more effective treatments, if not cures. Many significant gender differences were found that can help us individually tailor clinical management of disease processes. There are different techniques for gender identification such as face detection, voice detection, and human metabolism test, which have some weaknesses such as, the procedure of getting result is time-consuming and some are invasive. The main objective of this research is to explore a fast and non-invasive technique to identify human gender using urinalysis. This research examines the dielectrically properties of human urine at microwave frequencies as well as the quantitative analysis in the laboratory to identify differences between males and females urine. In this research, urine samples were collected from 60 healthy subjects (30 males and 30 females) in age group between 20-30 years. The permittivity analysis were carried out in less than 1½ hours after collecting the samples and Vector Network Analyzer was used to measure the permittivity of urine in the frequencies between 10Mhz-20GHz. The data obtained from Vector Network Analyzer, dielectric constant and loss factor, were plotted and analyzed using the MSExcel and SPSS. The obtained results show that there is a significant difference in permittivity, loss factor, and loss tangent, between males and females in different frequencies, which resulted in identifying human gender. This research shows that using the permittivity of urine can be used as one of the fast and non-invasive techniques to identify the human gender.